2014
DOI: 10.17221/83/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Potential of natural regeneration of Quercus robur L. in floodplain forests in the southern part of the Czech Republic

Abstract: ABSTRACT:The most common way of pedunculate oak regeneration on the floodplain sites in the Czech Republic is artificial regeneration by clear-cutting. However, what is the real potential of natural regeneration of pedunculate oak? In our research object (3,355 ha of floodplain forest in the southern part of the Czech Republic -Zidlochovice region), we inventoried about 8 ha of successful natural regeneration of pedunculate oak with density ranging between 15,000 and 100,000 individuals per ha on the plots aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…During the survey of 3,505 hectares of floodplain oak forests in the southern part of the Czech Republic, Dobrovolný (2014) found only 8 hectares of the area with sufficient natural reproduction of pedunculate oak of 15-100 thousand stems ha -1 after felling. The study of natural oak reproduction under the stand canopy in different lighting conditions has shown that the largest number of the reproduction (more than 10 thousand stems ha -1 ) was found near the forest margin at a distance of 18 m from the edge at the illumination of above 24%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the survey of 3,505 hectares of floodplain oak forests in the southern part of the Czech Republic, Dobrovolný (2014) found only 8 hectares of the area with sufficient natural reproduction of pedunculate oak of 15-100 thousand stems ha -1 after felling. The study of natural oak reproduction under the stand canopy in different lighting conditions has shown that the largest number of the reproduction (more than 10 thousand stems ha -1 ) was found near the forest margin at a distance of 18 m from the edge at the illumination of above 24%.…”
Section: Resultsmentioning
confidence: 99%
“…It will allow predicting their further development and preserving genetic potential. This problem becomes significant due to the current gradual warming and aridization of climate and the dynamic increase in the area of the nature reserve fund, the majority of which are tree stands with oak in their composition (Dobrowolska, 2008;Dobrovolný, 2014;Annighöfer et al, 2015;Tkach et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of natural oak regeneration depends on many factors, such as the number of oaks in the stand and their age, the relative density of stocking, the acorn yield, sufficient heat, moisture, and light, and the development of shrub and grass layers (Vedmid et al, 2008;Kharchenko & Kharchenko, 2012;Ligot et al, 2013;Dobrovolný, 2014;Levchenko, 2014;Tkach et al, 2014;Annighoefer et al, 2015;Sendonin, 2015;Sevillano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Întreaga literatură consultată, atât din România (Drăcea 1920-1921, Negulescu și Săvulescu 1965, Haralamb 1967, Constantinescu 1973, Stănescu 1979, Stănescu et al 1997 2011), atât în tinerețe, cât și ca arbore adult. Acest fapt creează mari probleme pentru regenerarea naturală a speciei, deoarece exemplarele tinere rezistă sub masivul închis al arboretului doar 2-3 ani, apoi se autorecepează repetat, până se usucă definitiv (Petcuț 1942, Negulescu și Săvulescu 1965, Constantinescu 1973, Stănescu 1979, Stănescu et al 1997, Dobrovolný 2014. Aceasta face ca puieții de stejar să trebuiască a fi eliberați complet de acoperișul de sus sau lateral al arboretului parental după cel mult 4 (5) ani (Vlad 1954, în Vlad 2007, Haralamb 1967Boudru 1989).…”
Section: Temperamentul Specieiunclassified